Genome-wide identification, characterization and expression pattern analysis of HAK/KUP/KT potassium transporter gene family in potato - Liu, Kun; Qin, Yonglin; Wu, Lan; Yi, Rong; Shi, Xiaohua; Yu, Jing; Shi, Xiaohong; Dong, Wenzhuo; Jia, Liguo; Fan, Mingshou (Frontiers in Plant Science, 2025)
The HAK/KUP/KT (High-affinity K+ transporters/K+ uptake permeases/K+ transporters) is the largest and most dominant potassium transporter family in plants, playing a crucial role in various biological processes. However, our understanding of HAK/KUP/KT gene family in potato (Solanum tuberosum L.) remains limited and unclear. In this study, 24 HAK/KUP/KT genes (StHAKs) were identified through a genome-wide analysis and were found to be unevenly distributed across ten chromosomes. Based on phylogenetic analysis, these StHAK gene family members were classified into four distinct clusters. All StHAK protein sequences contained the conserved motifs and domains. Promoter cis-acting elements analysis revealed that most StHAK gene family members in potatoes were associated with responses to light and hormones such as abscisic acid or methyl jasmonate, however, many motifs responsive to hormones and stress conditions have not been clearly studied or reported in plants. Synteny analysis suggested that 33, 19, 8, 1 StHAK genes were orthologous to those in soybean, cassava, Arabidopsis and rice, respectively. The previously published RNA-seq results, transcriptomic data and qRT-PCR experiments indicated that the expression profiles of these StHAK genes were tissue-specific and were influenced by multiple factors, including biotic and abiotic stress, hormone, potassium fertilizer. To provide a clear and convenient view of StHAK gene expression across different tissues in potato, we generated a cartoon heatmap to vividly illustrate the tissue-specific expression of StHAK genes, which is unprecedented in the gene family analysis of potato. At last, we identified genes such as StHAK8, StHAK14, and StHAK22 with high expression in potato tubers using qRT-PCR, suggesting their potential involvement in tuber growth and development. This can contribute to a deeper understanding of the mechanism of potassium absorption and transportation in potatoes. It has laid a solid theoretical foundation for the genetic regulation of potassium nutritional efficiency in potatoes and the breeding of potato varieties with high potassium efficiency.